Non-synonymous Single Nucleotide Polymorphisms (SNPs) on Growth Differentiation Factor 9 as candidate gene for reproduction in Indonesian local cattle - IRMA IRMA; SITI DARODJAH RASAD; NENA HILMIA; CECE SUMANTRI (Society for Indonesian Biodiversity, 2024)
Abstract. Irma, Rasad SD, Hilmia N, Sumantri C. 2024. Non-synonymous Single Nucleotide Polymorphisms (SNPs) on Growth Differentiation Factor 9 as candidate gene for reproduction in Indonesian local cattle. Biodiversitas 25: 4011-4019. Reproduction is a biological process that plays an essential role in livestock production. In mammals, the tendency to spontaneously conceive and maintain an embryo is a complex biological process affected by environmental and genetic factors, such as Growth Differentiation Factor 9 (GDF9). Therefore, this study aims to analyze the diversity of the GDF9 gene in the three breeds of cattle (Bos taurus), namely Peranakan Ongole (PO), Belgian Blue (BB), and its crossbreed (BB×PO) by molecular sequencing. A total of 20 blood samples were taken from cattle in the Livestock Embryo Centre, Bogor, Indonesia. DNA was extracted with genomic kit protocol followed by Polymerase Chain Reaction (PCR). Single nucleotide polymorphisms (SNPs) were then analyzed using Sanger sequencing. Sequence analysis was performed using Bio-Edit, Finch TV, and Molecular Evolutionary Genetic Analysis (MEGA) software. Variables analyses were allele and genotype frequency. The results showed that there were five non-synonymous mutations, namely c.589T>G (rs525937888), c.659T>G, c.974C>G, c.1105T>A, and c.1358G>A. These missense mutations altered the amino acid of GDF9 protein at position p.197Phe>Val, p.220Leu>Arg, p.325Ser>Cis, p.369Trp>Arg, and p.453Arg>His, respectively. The results also showed that the mutation prevalence wasigher in Peranakan Ongole compared to Belgian Blue and its crossbreed.